Ischemic neurons prevent vascular regeneration of neural tissue by secreting semaphorin 3A - Joyal, Jean-Sébastien; Sitaras, Nicholas; Binet, François; Rivera, Jose Carlos; Stahl, Andreas; Zaniolo, Karine; Shao, Zhuo; Polosa, Anna; Zhu, Tang; Hamel, David; Djavari, Mikheil; Kunik, Dario; et al. (Blood, 2011)
The failure of blood vessels to revascularize ischemic neural tissue represents a significant challenge for vascular biology. Examples include proliferative retinopathies (PRs) such as retinopathy of prematurity and proliferative diabetic retinopathy, which are the leading causes of blindness in children and working-age adults. PRs are characterized by initial microvascular degeneration, followed by a compensatory albeit pathologic hypervascularization mounted by the hypoxic retina attempting to reinstate metabolic equilibrium. Paradoxically, this secondary revascularization fails to grow into the most ischemic regions of the retina. Instead, the new vessels are misdirected toward the vitreous, suggesting that vasorepulsive forces operate in the avascular hypoxic retina. In the present study, we demonstrate that the neuronal guidance cue semaphorin 3A (Sema3A) is secreted by hypoxic neurons in the avascular retina in response to the proinflammatory cytokine IL-1β. Sema3A contributes to vascular decay and later forms a chemical barrier that repels neo-vessels toward the vitreous. Conversely, silencing Sema3A expression enhances normal vascular regeneration within the ischemic retina, thereby diminishing aberrant neovascularization and preserving neuroretinal function. Overcoming the chemical barrier (Sema3A) released by ischemic neurons accelerates the vascular regeneration of neural tissues, which restores metabolic supply and improves retinal function. Our findings may be applicable to other neurovascular ischemic conditions such as stroke.